Pharmacognostical and Pharmaceutical Analysis of Amalaka Rasayana Churna-A Polyherbal Ayurveda Formulation - Chandran, Amal Satheesa; Patil, Ashok; Kumar, Sanjiv; Sreenikakumar, Padmaveer Puthiyidam; Kaimal, Sreeja Kaimal Vijayakumara (International Journal of Pharmaceutical Investigation, 2026)
Background Amalaka Rasayana Churna (ARC) is a polyherbal Ayurvedic formulation consisting of Amalaki (Emblica officinalis Gaertn.), Pippali (Piper longum L.), Ghrita (ghee), Madhu (honey), and Sarkara (sugar) traditionally used for rejuvenation, longevity, and overall health enhancement. Objectives This study aims to evaluate the phytochemical composition, nutritional profile, and antioxidant activity of ARC through modern pharmaceutical-analytical methods to validate traditional claims. Materials and Methods The raw ingredients for ARC were sourced from a GMP-Certified Ayurveda Pharmacy and authenticated at an AYUSH-certified Central Research Facility. Various analytical methods, including preliminary phytochemical screening and Thin Layer Chromatography (TLC) were conducted at the KLE Shri B. M. K. Ayurveda Mahavidyalaya. Antioxidant activity, High Performance Thin Layer Chromatography (HPTLC) and nutritional analysis was performed at CARe Keralam Ltd., to assess the energy content, macronutrients, and bioactive compounds present in the formulation. Results The pharmaceutical-analytical evaluation showed that ARC has a semi-solid, blackish appearance, with a sour taste and an acidic pH of 2.43. The formulation exhibited a high water-soluble extractive value (86.596%) and significant antioxidant activity with an IC50 value of 29.72 mg/kg. Phytochemical analysis revealed the presence of carbohydrates, reducing sugars, flavonoids, tannins, steroids, alkaloids, and glycosides. The HPTLC analysis at 254 nm revealed nine distinct peaks, indicating the presence of multiple bioactive compounds. Nutritional analysis showed high carbohydrate content (90.9%) and significant sugar (45.77%), with minimal fat (0.35%) and protein (0.64%). Conclusion The pharmaceutical and analytical evaluation of Amalaka Rasayana Churna (ARC) confirms its rich phytochemical composition, and potent antioxidant activity. The formulation supports longevity, immunity, and overall rejuvenation. Analytical assessments validate its traditional Ayurvedic claims, highlighting its potential as a therapeutic drug. ARC’s antioxidant and immunomodulatory properties make it a promising natural supplement for managing oxidative stress, promoting well-being and longevity.
Keywords: Antioxidant; Ayurveda; Pharmaceutical; Rasayana; Traditional Medicine.